Processo de alcoolização em uma comunidade Yanomami de Roraima: o caso dos Yawaripë de Xikawa - Silva, Elizene Miranda da (2014)
This work is a study about the use of alcoholic beverages by the Yawari, Yanomami sub-group, inhabitants of the Ajarani River region, Roraima, Brasil, seeking to frame them on the historic context, social and cultural dynamics of the interethnic relationships. The methodological theoretical referential to understand the theme was based on the “integrative proposal”, which link three conceptual lines: dependence, alcoholization process and problems related to the use of alcoholic beverages. In applying this search it was chosen the qualitative method, privileging the observation and deep interview questions, based in reference works of authors in anthropology (Yanomami’s ethnography) collective health and epidemiology. Bibliographic research and consultations on websites of governmental organizations and non governmental organizations were undertaken. The interviews were applied to local leaders, indians and other people who lived or worked for many years with the Yanomami. From this study, it was possible to identify the associate factors of consumption, strategies to get the beverages and to refrain the abuse of alcohol, the consumed substances, the circumstances, motivations and senses attributed to use of alcoholic beverages by indians. Among the three conceptual lines, the Yawari were not identified with dependence syndrome to the use of alcohol; as a result of the problems related with excessive use of alcohol aggravating of health (physical and psychological) of individuals were verified. It was also identified some positive and negative views that were related to the use of alcoholic beverages associated to behaviour and internal rules. The misuse of alcohol in the researched community is a heterogeneous and collective phenomenon that play a constructive and socializing function, but it was also related to the negative identity, to the prejudice of the surrounding society, to the social, cultural and economic degradation of the community.